Dampak Bullying Di Lingkungan Sekolah Terhadap Perkembangan Psikologis - Em Aginta Putri (Indo Publishing, 2026)
In the current era, social issues often present children as victims in the media. Bullying is one of these social problems. This is very sad in places where children should feel safe and protected. This is in line with Law Number 23 of 2002 concerning child protection, which states that every child has the right to live, grow, develop, and participate properly in accordance with human dignity, as well as to receive protection from violence and discrimination. The method used in this research is a qualitative method with a descriptive approach with the type of research being a literature review. A literature review is the collection of information or written works that are library-based in nature. The collection of information is carried out by reviewing several written sources, namely journals, books, and other sources that are certainly in accordance with the research object. 1. Forms of bullying behavior in schools Bullying behavior is an act of violence that is intentionally or unintentionally carried out by an individual or a group, either verbally or physically. Bullying is a type of aggressive behavior in which an individual or a weaker group experiences psychological or physical pressure. The perpetrators are those who bully others and believe that they have the authority to do anything to their victims. And it is usually carried out by one person or a group of people. 2. The impact of bullying on psychological aspects The impact of bullying behavior on its victims can affect the physical and psychological condition of the victims, and there are even victims who feel depressed and withdraw from their surrounding social environment. Bullying behavior only makes children feel afraid, threatened, have low self-esteem, and feel worthless, have difficulty concentrating while learning, have difficulty socializing with their environment, do not want to go to school, have difficulty socializing, and become individuals who lack self-confidence, have difficulty thinking, and experience a decline in academic achievement. Talking about bullying is always related to an action or behavior of an individual or group toward other individuals or groups. Usually, bullying appears in various forms, namely verbal bullying, physical bullying, and cyberbullying. Bullying is essentially destructive and damaging. Bullying is an act of abuse of power carried out by an individual or a group. The parties who carry out bullying do not only mean strong in physical size but also strong in mental capacity. In this case, victims of bullying are unable to defend themselves because they have weak physical and mental conditions.